The transcriptome of the early life history stages of the California Sea Hare Aplysia californica - Fiedler, T. J. (2010)
Aplysia californica is a marine opisthobranch mollusc used as a model organism in neurobiology for cellular analyses of learning and behavior because it possesses a comparatively small number of neurons of large size. The mollusca comprise the second largest animal phylum, yet detailed genetic and genomic information is only recently beginning to accrue. Thus developmental and comparative evolutionary biology as well as biomedical research would benefit from additional information on DNA sequences of Aplysia. Therefore, we have constructed a series of unidirectional cDNA libraries from different life stages of Aplysia. These include whole organisms from the egg, veliger, metamorphic, and juvenile stages as well as adult neural tissue for reference. Individual clones were randomly picked, and high-throughput, single pass sequence analysis was performed to generate 7971 sequences. Of these, there were 5507 quality-filtered ESTs that clustered into 1988 unigenes, which are annotated and deposited into GenBank. A significant number (497) of ESTs did not match existing Aplysia ESTs and are thus potentially novel sequences for Aplysia. GO and KEGG analyses of these novel sequences indicated that a large number were involved in protein binding and translation, consistent with the predominant biosynthetic role in development and the presence of stage-specific protein isoforms.